2019
DOI: 10.22271/ortho.2019.v5.i2h.53
|View full text |Cite
|
Sign up to set email alerts
|

Functional outcome of surgical management in schatzker type V, VI tibial plateau fractures with locking compression plate

Abstract: Tibial plateau fractures are one of the commonest intra articular fractures. Results from indirect coronal or direct axial compressive forces. Among Tibial plateau fractures, Schatzker type V and VI tibial fractures are complex injuries, usually treated with open reduction and internal fixation (ORIF) using LCP plates. AIM: This study was done to determine functional outcome and the complications of Schatzker V and VI tibial plateau fractures treated with LCP plates with a regular follow-up of 18 months. Mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
1
0
0
Order By: Relevance
“…Study by Hong-Wei Chen et al, in 2015 on posterior tibial plateau fractures assessed postoperative outcome by modified Rasmussen functional scoring system showed that 28 (72%) cases had excellent results, 8 (20%) cases had good results and 3 (8%) cases had fair results and none of the cases had poor results. 3 Manikandan N et al, in 2019 in their study on complex tibial plateau fractures observed excellent results in 55%, good in 40%, fair in 5% and none of the cases had poor results 4 Modified Rasmussen score of our study showed comparable results with the different studies on tibial plateau fractures treated with locking compression plate 5 . In similar studies Gavhale SV et al, (2014) observed excellent results in 56.6%, good in 30% and fair in 13.3% patients 6 .…”
Section: Discussionsupporting
confidence: 77%
“…Study by Hong-Wei Chen et al, in 2015 on posterior tibial plateau fractures assessed postoperative outcome by modified Rasmussen functional scoring system showed that 28 (72%) cases had excellent results, 8 (20%) cases had good results and 3 (8%) cases had fair results and none of the cases had poor results. 3 Manikandan N et al, in 2019 in their study on complex tibial plateau fractures observed excellent results in 55%, good in 40%, fair in 5% and none of the cases had poor results 4 Modified Rasmussen score of our study showed comparable results with the different studies on tibial plateau fractures treated with locking compression plate 5 . In similar studies Gavhale SV et al, (2014) observed excellent results in 56.6%, good in 30% and fair in 13.3% patients 6 .…”
Section: Discussionsupporting
confidence: 77%